Purification and characterization of putative alkaline [Ni-Fe] hydrogenase from unicellular marine green alga, tetraselmis kochinensis NCIM 1605 - Bhosale, Siddharth H.; Pant, A.; Khan, Mohammad Islam (Microbiological Research, 2009)
Hydrogenase enzyme from the unicellular marine green alga Tetraselmis kochinensis NCIM 1605 was purified 467 fold to homogeneity. The molecular weight was estimated to be similar to 89kDa by SDS-PAGE. This enzyme consists of two subunits with molecular masses of similar to 70 and similar to 19 kDa. The hydrogenase was found to contain 10 g atoms of Fe and 1 g of atom of Ni per mote of protein. The specific activity of hydrogen evolution was 50 mu mol H-2/mg/h of enzyme using reduced methyl viologen as an electron donor. This hydrogenase enzyme has pl value similar to 9.6 representing its alkaline nature. The absorption spectrum of the hydrogenase enzyme showed an absorption peak at 425 nm indicating that the enzyme had iron-sulfur clusters. The total of 16 cysteine residues were found per mote of enzyme under the denaturing condition and 20 cysteine residues in reduced denatured enzyme indicating that it has two disulfide bridges. (C) 2007 Published by Elsevier GmbH.
Keywords: Characterization; Chemical modification; Ni-Fe hydrogenase; Tetraselmis kochinensis; Unicellular green algae

Active pharmaceutical ingredient (api) from an estuarine fungus, microdochium nivale (Fr.) - Bhosale, Siddharth H.; Patil, K. B.; Parameswaran, P. S.; Naik, C. G.; Jagtap, T. G. (Journal of Environmental Biology, 2011)
Various marine habitats sustain variety of bio-sources of ecological and biotech potentials. Pharmaceutical potential compound Cyclosporine A was reported from marine fungus Microdochium nivale associated with Porteresia coarctata, a marine salt marsh grass from mangrove environment distributed along the Central West Coast (CWC) of India. This study involves association of M. nivale with P. coarctata plant, fermentation conditions, purification of Cyclosporine A, chemical characterization etc. Its antifungal inhibition and MIC (Minimum inhibitory concentration) against Aspergillus strains (A. niger, A. japonicus, A. fresenii), yeasts and dermatophytes (Candida sp., Cryptococcus neoformans, Trichophyton mentagrophytes, T tonsurans, T violaceum, Microsporium gypsum and Fusarium sp.) were evaluated. However, the MIC against A. japonicus, C. neoformans, Candida sp. and T. tonsurans were confirmed to be as low as 12.5-25 mg disc(-1). The antifungal properties of Cyclosporine A against Aspergillus species, yeast and dermatophytes revealed that Cyclosporine A would be a potential compound for life threatening diseases caused by above fungi in both human and animals. Furthermore, we have reported herewith another source of Cyclosporin A derived from filamentous fungus, M. nivale. occurring in marine environment.
Keywords: antifungal; Cyclosporine A; Estuarine environment; Microdochium nivale

Fluorescence resonance energy transfer from tryptophan to folic acid in micellar media and deionised water - Mote, U. S.; Patil, S. R.; Bhosale, Siddharth H.; Han, Sung-Hwan; Kolekar, G. B. (Journal of Photochemistry and Photobiology B-Biology, 2011)
The fluorescence resonance energy transfer (FRET) from tryptophan (Trp) to folic acid (FA) in aqueous sodiumdodecyl sulphate, cetyltrimethyl ammonium bromide, and Brij-35 as well as deionised water was investigated using steady state and time resolved fluorescence techniques. The data obtained from steady state fluorescence spectral studies and time resolved measurement indicated that the FRET from Trp to FA occurred most effectively in aqueous sodium dodecyl sulphate micellar solutions. The distance between Trp and FA were evaluated. Binding constant, number of binding sites and thermodynamic parameters were determined for Trp-FA interactions in deionised water. The values of the thermodynamic parameters suggest that the hydrophobic forces and hydrogen bonding are the key interacting forces between Trp-FA interaction. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Fluorescence quenching; Fluorescence resonance energy transfer (FRET); Folic acid; Foster theory; Stern-Volmer plot; Tryptophan

Conformational transitions of the catalytic domain of heme-regulated eukaryotic initiation factor 2 alpha kinase, a key translational regulatory molecule - Sreejith, R. K.; Suresh, C. G.; Bhosale, Siddharth H.; Bhavnani, Varsha; Kumar, Avinash; Gaikwad, Sushama M.; Pal, Jayanta K. (Journal of Fluorescence, 2012)
In mammalian cells, the heme-regulated inhibitor (HRI) plays a critical role in the regulation of protein synthesis at the initiation step through phosphorylation of a-subunit of the eukaryotic initiation factor 2 (eIF2). In this study we have cloned and performed biophysical characterization of the kinase catalytic domain (KD) of rabbit HRI. The KD described here comprises kinase 1, the kinase insertion domain (KI) and kinase 2. We report here the existence of an active and stable monomer of HRI (KD). The HRI (KD) containing three tryptophan residues was examined for its conformational transitions occurring under various denaturing conditions using steady-state and time-resolved tryptophan fluorescence, circular dichroism (CD) and hydrophobic dye binding. The parameter A and phase diagram analysis revealed multi-state unfolding and existence of three stable intermediates during guanidine hydrochloride (Gdn-HCl) induced unfolding of HRI (KD). The protein treated with 6 M Gdn-HCl showed collisional and static mechanism of acrylamide quenching and the constants (K-sv=3.08 M-1 and K-s=5.62 M-1) were resolved using time resolved fluorescence titration. Based on pH, guanidine hydrochloride and temperature mediated transitions, HRI (KD) appears to exemplify a rigid molten globule-like intermediate with compact secondary structure, altered tertiary structure and exposed hydrophobic patches at pH 3.0. The results indicate the inherent structural stability of HRI (KD), a member of the class of stress response proteins.
Keywords: Circular dichroism (CD); eIF2 alpha kinase; Heme-regulated inhibitor; Molten globule; Steady-state and time-resolved fluorescence

Zinc inhibits glycation induced structural, functional modifications in albumin and protects erythrocytes from glycated albumin toxicity - Tupe, Rashmi; Kulkarni, Amruta; Adeshara, Krishna; Sankhe, Neena; Shaikh, Shamim; Dalai, Sayli; Bhosale, Siddharth H.; Gaikwad, Sushama M. (International Journal of Biological Macromolecules, 2015)
The present work aims to investigate the concentration and time dependant effect of zinc on the in vitro non enzymatic modifications of albumin by diabetic levels of glucose. Further, preventive and curative effect of zinc was studied by adding zinc before and after initiation of glycation respectively. Glycation of albumin was done at different concentrations of zinc (125, 250 and 500 mu M) at different time intervals (21,28 and 35 days) with appropriate controls. The antiglycation potential of zinc was assessed by estimating different markers of albumin glycation (fructosamines, carbonyls, bound sugar, AGEs), structural modifications (free amino, thiol group, beta amyloid, native PAGE, ANS binding, fluorescence lifetime decay and CD analysis) and functional properties (antioxidant activity, hemolysis). Zinc at highest concentration (500 mu M) significantly reduced modifications of albumin which was comparable to aminoguanidine and also protected secondary and tertiary structure of albumin after 28 days of incubation. Zinc exhibited significant protective effect on erythrocytes by inhibiting hemolysis. Thus the present study indicate preventive mode of albumin glycation inhibition by zinc. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Albumin; Erythrocytes; Glycation

Functional and conformational transitions of mevalonate diphosphate decarboxylase from Bacopa monniera - Shakeel, Abbassi; Patel, Krunal; Khan, Bashir Mohammad; Bhosale, Siddharth H.; Gaikwad, Sushama M. (International Journal of Biological Macromolecules, 2016)
Functional and conformational transitions of mevalonate diphosphate decarboxylase (MDD), a key enzyme of mevalonate pathway in isoprenoid biosynthesis, from Bacopa monniera (BmMDD), cloned and overexpressed in Escherichia coli were studied under thermal, chemical and pH-mediated denaturation conditions using fluorescence and Circular dichroism spectroscopy. Native BmMDD is a helix dominant structure with 45% helix and 11% sheets and possesses seven tryptophan residues with two residues exposed on surface, three residues partially exposed and two situated in the interior of the protein. Thermal denaturation of BmMDD causes rapid structural transitions at and above 40 degrees C and transient exposure of hydrophobic residues at 50 degrees C, leading to aggregation of the protein. An acid induced molten globule like structure was observed at pH 4, exhibiting altered but compact secondary structure, distorted tertiary structure and exposed hydrophobic residues. The molten globule displayed different response at higher temperature and similar response to chemical denaturation as compared to the native protein. The surface tryptophans have predominantly positively charged amino acids around them, as indicated by higher K-SV for IC as compared to that for CsCl. The native enzyme displayed two different lifetimes, vi (1.203 +/- 0.036 ns) and tau 2 (3.473 +/- 0.12 ns) indicating two populations of tryptophan. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Aggregation; CD spectroscopy; Fluorescence quenching; Mevalonate diphosphate decarboxylase; Unfolding